Foreign economic activity of Ukraine in the field of organic production during the war (Economics and region, 2024)
The article examines the latest trends in the dynamics of changes in the foreign economic activity of organic producers, taking into account the impact of military operations on the territory of Ukraine, and also identifies the main importers of Ukrainian organic products in 2022, including such countries as: Austria, Great Britain, Italy, Lithuania, Poland , the Netherlands, Germany, the USA, Switzerland and the Czech Republic. In addition, the work examines the dynamics of the export of organic products from Ukraine to exporting countries for 2022-2024. and structured according to the main types of products. International projects on the development of organic production and circulation of organic products in Ukraine were considered. With the support of the Ministry of Agrarian Policy and in cooperation with participants of the organic sector and international development partners, various activities are taking place to promote the development of the organic market in Ukraine. Organic production in Ukraine demonstrated resistance to the challenges of war. It was established that the export of organic products from Ukraine is growing, and the import is gradually recovering. In the first 5 months of 2024, the export of organic products from Ukraine amounted to 105,000 tons worth 96 million US dollars. This is 12% more in volume and 8% more in value compared to the same period in 2023. Such data indicate that Ukraine is maintaining the dynamics of growth in the export of organic products. It is expected that by the end of 2024, the export of organic products from Ukraine will reach 300,000 tons worth 264 million US dollars. The obtained results are of significant practical importance, as they allow: to develop strategies and recommendations for increasing the efficiency of foreign economic activities of producers of organic products; to determine the main directions of support and development of the agro-industrial sector in the conditions of war; to increase the competitiveness of Ukrainian organic products on the world market; ensure the stability and growth of exports, which will contribute to the economic development of the country as a whole.
Keywords: agricultural industry; organic production; foreign economic activity; export; import